2019
DOI: 10.1002/macp.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light–Induced RAFT Polymerization of Methacrylate with 4‐(N,N‐diphenylamino)benzaldehyde as Organophotoredox Catalyst and the Effect of Temperature on the Polymerization

Abstract: With UV–vis absorption in the range of 270–435 nm, 4‐(N,N‐diphenylamino)benzaldehyde (DPAB) takes efficient photoreduction quench with 4‐cynao‐4‐(phenylcarbonothioylthio)pentanoic acid (CTP). The polymerization rates of methyl methacrylate (MMA) are 0.019, 0.056, and 0.102 h−1 at 33, 40, and 50 °C, respectively, in the presence of DPAB and CTP under visible‐light irradiation. Dark reaction produces no PMMA at 50 °C for 120 h. The living feature is demonstrated by linearly increasing Mn with the monomer convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…This phenomenon is also mentioned in the light induced RAFT polymerization catalyzed by aromatic aldehyde derivatives. [76]…”
Section: Chain Extension and Block Polymerization With Pma-ttp As Macro-raftmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is also mentioned in the light induced RAFT polymerization catalyzed by aromatic aldehyde derivatives. [76]…”
Section: Chain Extension and Block Polymerization With Pma-ttp As Macro-raftmentioning
confidence: 99%
“…[71] Recently, we have developed a series of aldehyde derivative catalysts, such as 4-methoxy benzaldehyde and 4-(N,N-diphenylamino) benzaldehyde, which can serve as effective photoredox catalysts for RDRP. [72][73][74][75][76] Compared to metal complexes, the polymerizations catalyzed with benzaldehydes are somewhat slow, and tertiary amine, such as N,N-dimethylaniline, could promote the polymerization significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these reactions, a well-controlled reversible degenerative radical polymerization of methacrylate has been demonstrated. 29 Very recently, DPAB as a photoredox catalyst was also successfully used in synthesis of α,ω-dithiol and α,ω-divinyl telechelic polythioether oligomers through thiol-ene click polymerization of 1,4-benzenedimethane (BDMT) and diethylene glycol divinyl ether (DEGVE). 30 Thiol-ene click polymerization is of great advantage in surface modification for its insensitive to moisture and oxygen, and the availability of various functional monomers 31 These surface-anchored polymeric coatings demonstrate intrinsic properties of polymers, such as flexibility, biocompatibility, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that 4‐( N , N ‐diphenylamino)benzaldehyde (DPAB) excited by visible‐light could be reductively quenched by a RAFT reagent 4‐cynao‐4‐(phenylcarbonothioylthio)pentanoic acid. Based on these reactions, a well‐controlled reversible degenerative radical polymerization of methacrylate has been demonstrated 29 . Very recently, DPAB as a photoredox catalyst was also successfully used in synthesis of α , ω ‐dithiol and α , ω ‐divinyl telechelic polythioether oligomers through thiol‐ene click polymerization of 1,4‐benzenedimethane (BDMT) and diethylene glycol divinyl ether (DEGVE) 30…”
Section: Introductionmentioning
confidence: 99%